Densities and viscosities of mixtures containing water, methanol and ethanol. Issue 1 (7th December 2021) - Aliaj, Fisnik Rr; Syla, Naim; Vatovci, Enis; Arbneshi, Tahir; Dalipi, Bashkim
Abstract : The experimental densities and viscosities are reported in this paper for the binary mixtures: water + methanol, water + ethanol and methanol + ethanol over the entire composition range at 293.15 K and atmospheric pressure. From these experimental data, the excess molar volumes, V E, and deviations in viscosity, Δη, were derived and fitted to the Redlich–Kister polynomial to determine the adjustable fitting parameters and standard deviations. The variation of excess and deviation properties with composition has been interpreted in terms of the molecular interactions between the components of the mixtures and structural effects. Additionally, various correlation models were applied to estimate the viscosities of the mixtures to test their validity for the mixtures being studied.